Pengaruh Persepsi Harga, Promosi, dan Kualitas Layanan terhadap Kepuasan Konsumen CV Simpatik Jaya Surabaya - Jaya, I Nyoman Ary Danan; Ida Ayu Sri Brahmayanti (Jurnal Nirta : Inovasi Multidisiplin, 2025)
The aim of this research is to study how perceptions of price, promotion and service quality impact customer satisfaction at CV Simpatik Jaya Surabaya. The CV Simpatik Jaya company provides swimming pool construction, gardening and other cleaning services. To compete in the market and maintain customer loyalty, customer satisfaction is very important for companies. Service quality, price perception, and promotions were chosen because they are considered to greatly influence customer satisfaction. This research was conducted quantitatively through survey methods. Data was collected using a purposive sampling technique by distributing questionnaires to 100 selected CV Simpatik Jaya consumers. To examine the relationship between the three independent variables—promotion, service quality, and price perception—and the dependent variable—consumer satisfaction, data analysis used multiple linear regression. The research results show that promotion and service quality have a significant and positive influence on consumer satisfaction. The results of this research indicate that effective promotions and superior service quality are important factors in increasing customer satisfaction at CV Simpatik Jaya. Therefore, companies must improve their informative and attractive promotional strategies and ensure consistent service quality to meet customer expectations. This study helps develop the company's marketing strategy. In addition, it can be a source of additional research. Keywords: Price perception, Promotion, Service Quality, and Customer Satisfaction.